Serum luteinizing hormone trajectories during ovarian stimulation and their outcomes of IVF/ICSI: a retrospective cohort study - Liu, Conghui; Wang, Jiawei; Tian, Jing; Chen, Shengyuan; Bao, Wei; Luo, Lei; Wu, Limin; Meng, Ye (Frontiers in Endocrinology, 2025)
BackgroundAn appropriate luteinizing hormone (LH) level during ovulation stimulation (OS) is important for positive in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) outcomes. Although the gonadotrophin-releasing hormone antagonist (GnRH-ant) protocol can inhibit a premature rise of LH, it remains ineffective in some patients. This study aimed to identify the characteristics of patients who shared similar underlying LH trajectories and to determine how different serum LH trajectories influence IVF/ICSI outcomes.MethodsThis study was a retrospective cohort study that included 2,716 patients who underwent GnRH-ant protocol for OS from 1 January 2017 to 31 June 2024. Multiple serum LH measurements during OS were collected. Group-based trajectory modeling was used to identify subgroups of participants who shared similar LH trajectories. Patients’ characteristics and IVF/ICSI outcomes across the identified LH trajectories were compared. Furthermore, linear and log-binomial regression models were used to assess the association of LH trajectories with IVF/ICSI and pregnancy outcomes.ResultsThree discrete LH trajectories were identified: persistently low (90.7%, n = 2,464), from middle to high (7.6%, n = 206), and up and down (1.7%, n = 46). Compared to patients with persistently low trajectory, a higher number of antral follicle counts (AFC) and level of basal LH were observed for patients with middle to high and up and down trajectories. Although a higher number of oocytes and embryos were found for patients with middle to high and up and down trajectories than those with persistently low trajectory, metaphase II oocytes and embryo formation rates were lower. Despite these differences, pregnancy outcomes after fresh embryo transfer were similar across the three trajectories.ConclusionsPatients with an elevated number of AFC and basal LH were more likely to exhibit unstable LH trajectories. Higher LH trajectories during ovarian stimulation were associated with a better quantity rather than the quality of oocytes or embryos.